2016
DOI: 10.1038/srep35785
|View full text |Cite
|
Sign up to set email alerts
|

The significance of linoleic acid in food sources for detritivorous benthic invertebrates

Abstract: Chemical composition of organic matter (OM) is a key driver for detritus consumption by macroinvertebrates and polyunsaturated fatty acid (PUFA) content is considered a candidate indicator of food palatability. Since traditionally used complex natural OM covaries in many quality attributes, it remains uncertain whether benthic invertebrates developed an actual preference for PUFA-rich food. Therefore we aimed to test the influence of the PUFA linoleic acid on OM consumption by aquatic macroinvertebrates using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…As for field experiments, although some authors [ 19 ] found exposure to light to stimulate decomposition in the field, their "shadow" treatment was artificial, as they covered the channel with cloth. Similarly, Vonk et al [ 59 ] found that, whereas in microcosms, invertebrates showed a preference for artificial substrate with poly-unsaturated fatty acids added, this effect could not be detected in the field, probably because it was overruled by unknown sources of variation. Priming could be more important in summer, when the differences in light availability between open and closed reaches are largest and the long baseflow periods make biological effects more marked.…”
Section: Discussionmentioning
confidence: 99%
“…As for field experiments, although some authors [ 19 ] found exposure to light to stimulate decomposition in the field, their "shadow" treatment was artificial, as they covered the channel with cloth. Similarly, Vonk et al [ 59 ] found that, whereas in microcosms, invertebrates showed a preference for artificial substrate with poly-unsaturated fatty acids added, this effect could not be detected in the field, probably because it was overruled by unknown sources of variation. Priming could be more important in summer, when the differences in light availability between open and closed reaches are largest and the long baseflow periods make biological effects more marked.…”
Section: Discussionmentioning
confidence: 99%
“…Such an endogenous ability to produce physiologically important PUFA would represent an important ecological adaptation for the giant tubeworm R. pachyptila to environments with little input of these compounds via major primary producers such as photosynthetic microalgae (Liu et al 2017a). Similarly, the aquatic invertebrate communities largely composed of annelids, molluscs and arthropods dominate benthic ecosystems, and therefore possession of ωx desaturases appears as an advantageous trait to counteract the naturally poor availability of n-3 PUFA in such environments (Vonk et al 2016).…”
Section: Other Invertebrates (Rotifers Molluscs Annelids and Arthromentioning
confidence: 99%
“…The high proportions of LIN, and even stearic acid (18:0) and oleic acid (18:1ω9), in periphyton and all feeding groups also indicated that detrital food sources were probably quite abundant, even as a component of periphyton, which can be comprised of >30% allochthonous material (Rasmussen, 2010). In addition, fungi, especially hyphomycetes, can enhance the nutritional quality of detritus and were probably important contributors to the high proportions of LIN, ALA, oleic TA B L E 4 Spearman correlations of the proportions of major fatty acid (FA) groups in periphyton and invertebrate feeding groups with urban-related environmental variables acid, and stearic acid (18-C FAs) in shredders and even in other FFGs (Arce-Funck, Bec, Perrière, Felten, & Danger, 2015;Taube, Ganzert, Grossart, Gleixner, & Premke, 2018;Vonk, van Kuijk, van Beusekom, Hunting, & Kraak, 2016). Quantification of major periphyton groups could provide additional insights in the future (e.g., Whorley & Wehr, 2016a), given that increased abundances of chlorophyte and cyanobacteria taxa associated with greater amounts of nutrients also could contribute to greater Σω6 FAs, LIN, and the ω3 ALA (Galloway & Winder, 2015;Guo et al, 2016a;Hill et al, 2011).…”
Section: Comparisons Of Fas Among Periphyton and Macroinvertebratesmentioning
confidence: 99%